(NmETOD GRANI^NYH INTEGRALXNYH URAWNENIJ (B:s (NwY^ISLITELXNYE ASPEKTY I PRILOVENIQ W MEHANIKE (B/s - (NwAJN[ELXBAUM(B, (Nw(B.(Nm(B.s; (NgOLXD[TEJN(B, (Nr(B.(Nw(B.s; (NkRUZ(B, (Nt(B.s; (NrICCO(B, (Nf(B.s ((NmOSKWA (B:s (NmIR(B,s, 1978)
(NsPISOK LIT(B.: (NS(B. 206 - 209s
Keywords: (NiNTEGRALXNYE URAWNENIQs; (NmEHANIKAs